2023
DOI: 10.1021/acs.joc.2c02413
|View full text |Cite
|
Sign up to set email alerts
|

Monomerization of Phthalocyanines in Water via Their Supramolecular Interactions with Cucurbiturils

Abstract: Aggregation of phthalocyanines (Pcs) represents a problematic feature that decreases the potential of these macrocycles in a number of applications. In this work, we present a supramolecular approach based on the interaction of aminoadamantyl-substituted Pcs with bulky and hydrophilic cucurbit[7]uril (CB[7]) to increase the levels of Pc monomers in water. A series of zinc(II) Pcs substituted at positions α or β by an aminoadamantyl substituent (with a different level of alkylation of nitrogen) were prepared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…However, one must carefully design the system in which ADA/CB[ n ] will be incorporated and estimate whether the final assembly would be too bulky and/or hydrophilic to enter the cells in sufficient amount as it was demonstrated in the case of four CB[7]s that were non-covalently attached to aminoadamantyl-substituted phthalocyanines (Pcs). 159 The study in question showed that supramolecular interaction between CB[7] with Pcs in water improved both fluorescence and singlet oxygen production. On the other hand, bioactivity decreased for at least an order of magnitude after host–guest interaction with CB[7], which was attributed to much lower uptake by cells due to the aforementioned reasons.…”
Section: Cucurbit[ N ]Urils In Drug Deliverymentioning
confidence: 99%
“…However, one must carefully design the system in which ADA/CB[ n ] will be incorporated and estimate whether the final assembly would be too bulky and/or hydrophilic to enter the cells in sufficient amount as it was demonstrated in the case of four CB[7]s that were non-covalently attached to aminoadamantyl-substituted phthalocyanines (Pcs). 159 The study in question showed that supramolecular interaction between CB[7] with Pcs in water improved both fluorescence and singlet oxygen production. On the other hand, bioactivity decreased for at least an order of magnitude after host–guest interaction with CB[7], which was attributed to much lower uptake by cells due to the aforementioned reasons.…”
Section: Cucurbit[ N ]Urils In Drug Deliverymentioning
confidence: 99%
“…Highly hydrophilic cyclodextrins and cucurbit[n]urils (CB[n]) were mostly utilized for the solubilization of various PS. 8 For example, CB [7], known to form stable inclusion complexes with organic cations, was used to increase water solubility and reduce aggregation of phthalocyanine, 9 porphyrin, 10 or methylene blue 11 PSs with various consequences (positive or negative) for the final photodynamic activity. Also, an opposite approach in delivering AIEgens (aggregationinduced emission fluorophores) attached to CB [7] was recently reported.…”
mentioning
confidence: 99%
“…(c) 1-Aminoadamantane and its analogues substituted on nitrogen atoms are known to form strong host-guest complexes with CB [7] having K a values in the range of 10 12 -10 15 M À1 . 9,21,22 Therefore, adamantyl (Ad) substituents have been placed on either meso position (1-3, one Ad) or on both styryl substituents (4 and 5, two Ads). This allowed us to evaluate the effect of one or two bulky and hydrophilic CB [7] molecules on the final BODIPY properties after the inclusion of Ad inside the macrocycle (Fig.…”
mentioning
confidence: 99%